2000
DOI: 10.1148/radiology.216.1.r00jl37260
|View full text |Cite
|
Sign up to set email alerts
|

US Evaluation of the Uterus in Patients with Postmenopausal Bleeding: A Positive Effect on Diagnostic Decision Making

Abstract: HSG and transvaginal US in patients with PMB improves diagnostic accuracy, clinical decision making, and the clinician's diagnostic certainty. In patients with benign causes of PMB, the absence of abnormality at HSG and a normal endometrial biopsy result may eliminate the need for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 22 publications
2
50
0
4
Order By: Relevance
“…The overall sensitivity, specificity, positive predictive value and negative predictive value of the procedure in this study were 92.8%, 81.8%,86% 90% respectively. This correlates well with results in the study conducted by Robert L.Bree et al (1) in which findings yielded a sensitivity of 98%,specificity of 88%, positive predictive value of 94%, and negative predictive value of 97%. In a study by Yildizhan er al (2) , sensitivity and specificity were 91.6% and 98.7% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The overall sensitivity, specificity, positive predictive value and negative predictive value of the procedure in this study were 92.8%, 81.8%,86% 90% respectively. This correlates well with results in the study conducted by Robert L.Bree et al (1) in which findings yielded a sensitivity of 98%,specificity of 88%, positive predictive value of 94%, and negative predictive value of 97%. In a study by Yildizhan er al (2) , sensitivity and specificity were 91.6% and 98.7% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…It occurs primarily after menopause and in most cases presents with vaginal bleeding [1]. However, postmenopausal vaginal bleeding is associated with endometrial neoplasia in only about 10% to 30% of the cases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is a common problem of perimenopausal or postmenopausal women. 15 A recent meta-analysis found that in postmenopausal women a transvaginal sonography result of 5mm or less endometrial thickness reduced the risk of disease by 84%. 16 but some pathology may be missed by it.…”
Section: Resultsmentioning
confidence: 99%